Impacts of climate change on agriculture and policy options for adaptation: The case of Vietnam - Yu, Bingxin; Zhu, Tingju; Breisinger, Clemens; Hai, Nguyen Manh (International Food Policy Research Institute, 2010)
Vietnam is likely to be among the countries hardest hit by climate change, mainly through rising sea levels and changes in rainfall and temperatures. Agriculture can be extensively affected by climate change, and designing effective adaptation strategies will be critical for maintaining food security, rural employment, and foreign exchange earnings. This paper examines these critical issues and thereby makes two contributions to the literature. First, we estimate the impacts of climate change on agricultural and water systems in Vietnam based on crop simulation, hydrological simulation, and river basin models. We then present a yield function approach that models technology advances and policy interventions to improve rice productivity and mitigate the impact of climate change, using a multilevel mixed effects model. This two-pronged approach allows rice yield changes to be linked with both biophysical and socioeconomic conditions. The results indicate that rice production is likely to be severely compromised by climate change. However, investment in rural infrastructure, such as irrigation and road, and human capital can mitigate the negative impacts of climate change. Due to substantial regional variations in impacts and responses, localized policy packages will be key for effective mitigation. Government policies targeting ethnic-minority and poor communities will be especially important components of climate change adaptation strategies.